Pengaruh Peluang Karir, Kompetensi dan Komitmen Organisasi terhadap Kinerja Penyuluh Keluarga Berencana Melalui Motivasi Kerja Sebagai Variabel Intervening: Studi pada Kantor Perwakilan Badan Kependudukan dan Keluarga Berencana Nasional di Provinsi Sulawesi Barat - Dian Pancawaty; Madris Madris; Zainur Hidayah (Al-Buhuts, 2025)
This study aims to analyze the role of career opportunities, competencies, and organizational commitment on the performance of family planning counselors by including work motivation as a mediating variable at the West Sulawesi Provincial Office of the National Population and Family Planning Agency (BKKBN). This study is based on the importance of improving counselor performance in addressing the complexities of family planning services, which have not been fully explained by integrated individual and organizational factors in previous research. The study employed a quantitative approach with a sample of 205 family planning counselors selected via a survey. Data were analyzed using Partial Least Squares-based Structural Equation Modeling (SEM-PLS). The results indicate that career opportunities, competencies, and organizational commitment significantly enhance family planning counselors’ work motivation and performance. Furthermore, work motivation was found to act as a mediator that strengthens the influence of these three variables on performance. These findings confirm that the integration of career development factors, individual capacity, and organizational commitment is a critical determinant in improving counselors’ performance. Theoretically, this study enriches the literature on public sector organizational behavior by emphasizing the mediating role of work motivation in performance models. Practically, the research results provide implications for policymakers within the BKKBN to design performance improvement strategies based on strengthening motivation and human resource development.